Analisis Lawang Sewu sebagai Destinasi Dark Tourism terhadap Pengalaman Wisatawan Nusantara (Studi Kasus Bangunan Bersejarah Lawang Sewu) - Fahrurozy Darmawan; Novinda Mellina; Yustisia P. Mbulu (Fakultas Pariwisata Universitas Pancasila, 2018)
This research’s purpose is to identify and analyze how Lawang Sewu as a Dark Tourism Destination towards domestic tourists’ motivation. So it can explain that Lawang Sewu is indicated as a dark tourism destination towards domestic tourists’ exoerience. The research design used in this research is qualitative descriptive, by making use of the secondary and primary data. The data collection methods that used are observation in Lawang Sewu, interview with the Dinas Pariwisata Kota Semarang, Lawang Sewu Manager, Lawang Sewu tour guide and domestic tourists, documentation, and purposive sampling which is the technique in determining the informants. The results of this research show that the attraction that is dark tourism indicated in Lawang Sewu is the underground room and domestic tourists’ experience who visit Lawang Sewu varies, before visiting, the tourists felt curious and when they are at Lawang Sewu they experience shock.